Response of coccolithophore communities to oceanographic and atmospheric processes across the North- and Equatorial Atlantic - Guerreiro, Catarina V.; Ferreira, Afonso; Cros, Lluisa; Stuut, Jan-Berend; Baker, Alex; Tracana, Andreia; Pinto, Catarina; Veloso, Vera; Rees, Andrew P.; Cachão, Mário A. P.; Nunes, Telmo; Brotas, Vanda (Frontiers in Marine Science, 2023)
Changes in coccolithophore productivity in response to climate-driven ocean warming are likely to have cascading biogeochemical effects that feed back to the changing climate. This paper investigates the role (and interplay) of large-scale oceanographic and atmospheric processes across the North- and Equatorial Atlantic, including Saharan dust deposition, on the distribution of coccolithophore communities. The study is based on biological and hydrological data collected across the photic zone of the ocean, and aerosol data collected from the lower atmosphere, across 50°N–1°S during the Atlantic Meridional Transect in boreal Autumn of 2018 (AMT28), in synergy with Earth Observations. Results confirm existing understanding of the distribution of coccolithophore communities which are related to major meridional hydrological gradients across the North Atlantic. Dynamic, oxygenated and microphytoplankton-enriched waters at higher-latitudes were characterized by less diverse coccolithophore populations, dominated by placolith-bearing r-selected coccolithophores. In contrast, the heavily stratified and picoplankton-enriched waters of the subtropical gyre revealed more diverse populations, dominated by umbelliform coccolithophores and holococcolithophores at the surface, and by floriform taxa in the lower photic zone. Mean concentrations of 14.4×103 cells/L present in the North Atlantic Tropical Gyre Province (30–12°N), only slightly lower compared to 17.7×103 cells/L produced in the North Atlantic Drift province (50–40°N), provide a snapshot perspective on the importance of coccolithophore production in heavily stratified gyre conditions. Higher concentrations of 19’-Hexanoyloxyfucoxanthin (HexFuco) in regions of enhanced production of r-selected placolith-bearing species suggest that this pigment should not be generalized as a proxy for the entire coccolithophore community. Enhanced abundances of fast-blooming Emiliania huxleyi and Gephyrocapsa oceanica, and of cyanobacteria (including both picoplankton and N2-fixing Trichodesmium spp.) at the surface of the region of more persistent Saharan dust deposition (at 12-10°N) appeared to result from dust-born nutrient input. Underneath this stratified surface layer, enhanced productivity in the deep chlorophyll maximum (DCM) appeared decoupled from that on the surface, fueled by geostrophic eastward shoaling of the nutricline across the tropical North Atlantic. As this was the region of highest macronutrient concentrations measured along and below the nutricline, our data suggest that the NE tropical Atlantic may act as a permanent dust-born nutrient depocenter as previously hypothesized.